KOMPARASI HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DAN TIPE THINK PAIR SHARE - Christopher Makapuan; Anderson L Palinussa; Hanisa Tamalene (Science Map Journal, 2023)
This study aims to determine the comparison of student learning outcomes using the Student Facilitator and Explaining (SFE) Cooperative Learning Model and the Think Pair Share (TPS) Cooperative Learning Model on quadrilateral material in grade VII Christian Middle School Kusu-Kusu Sereh Ambon. The type of research used is experimental research (Experimental Research) with a Post Test Group Design research design. In this study, the population used was all students of class VII Kusu-Kusu Christian Middle School, Sereh Ambon, which consisted of 2 classes with a total of 40 students, selected using the Total Sampling technique. The instrument used in the study was in the form of test questions consisting of 5 description questions for the final test. The study made experimental class students one and experimental class two students using the Student Facilitator and Explaining (SFE) Cooperative Learning Model and Think Pair Share (TPS) Cooperative Learning Model on rectangular material. Based on the statistical analysis of the t-test, the value of Sig.(2-tailed) 0.124 is greater than = 0.05, so there is no significant difference between the two models. Furthermore, the Mean value in the Group Statistics table shows that the Mean value of Student Facilitator and Explaining is 65.92 and the Mean value of Think Pair Share is 57.77. These results can be proven that the superior learning model is the Student Facilitator and Explaining (SFE) Cooperative Learning Model